1975
DOI: 10.1111/j.1468-2958.1975.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions Speak Louder Than Words?sometimes

Abstract: Three telephone surveys conducted during different phases of the Vietnam War (N=401, 199, and 299, respectively) were conducted to determine how changes in events and in sources' actions relevant to those events affect the perceived credibility of various information sources. Data linking four sources (students, the Stanford University News Service, CBS News, and the White House) to three issues (air pollution, unemployment, the war) indicate that ascribed credibility: (a) increased with the purported objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Though it is post hoc speculation, one might consider a number of explanations for this finding, including the idea that younger people are more sensitized to the social conflict surrounding racial issues and racial groups. Previous research has demonstrated that people are inclined to be more skeptical as news coverage focuses on more controversial topics (Roberts and Leifer 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it is post hoc speculation, one might consider a number of explanations for this finding, including the idea that younger people are more sensitized to the social conflict surrounding racial issues and racial groups. Previous research has demonstrated that people are inclined to be more skeptical as news coverage focuses on more controversial topics (Roberts and Leifer 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Trust in media treatment of a particular issue declines, for example, when the issue is seen as more controversial (Roberts and Leifer 1975), or as bad news (Stone and Beell 1975). In an experiment with Arab and Israeli students, Vallone, Ross, and Lepper (1985) found that those notably partisan on Mideast issues perceived more bias-bias contrary to their own position-in media coverage of the so-called Beirut massacre (see also Perloff 1989).…”
Section: The Skeptical Dispositionmentioning
confidence: 96%
“…Indeed, situational factors such as attitude extremity (Gunther, 1988), issue importance (Gunther & Lasorsa, 1986), controversiality of the issue (Roberts & Leifer, 1975), good news versus bad news (Stone & Beell, 1975), and audience bias (Vallone, Ross & Lepper, 1985) have shown a relationship with media credibility evaluations.…”
Section: Introductionmentioning
confidence: 98%